IMMUNOLOGIC STUDIES OF AUTOIMMUNE DISEASE IN NZB/NZW F(1) MICE : I. BINDING OF FLUORESCEIN-LABELED ANTINUCLEOSIDE ANTIBODIES IN LESIONS OF LUPUS-LIKE NEPHRITIS - Seegal, B. C. (The Rockefeller University Press, 1969)
For the past 3 years NZB and NZW mice have been maintained by sister-brother matings from English breeder stock. NZB/NZW F(1) hybrids developed lupus-like nephritis during the 6th to 7th month and few survived beyond the 8th month. Renal tissues of these animals were examined with fluorescein-labeled antinucleoside sera, specific for thymine and cytosine, for the presence of denatured DNA in GCW, and with labeled antibody to mouse IgG for the presence of excess host globulin in the same areas. The following results have been obtained: (a) All 51 hybrids, over 5 months of age, had an excess of mouse globulin in GCW. 40 animals between the ages of 5 and 12 months showed, in the same areas, antigens which bound one or both of the antinucleoside antibodies. (b) Renal tissues of 19 NZB mice, 5–19 months old, and 27 NZW mice, 2–18 months old, were examined. Excess host globulin was seen in GCW of 13 NZB and 20 NZW animals. The tissues of only two old NZB mice, 14 months of age, bound antinucleoside antibody but none of the other animals did. The association of rapidly fatal lupus-like nephritis in NZB/NZW F(1) mice with denatured DNA and mouse globulin in GCW supports the hypothesis involving this antigen-antibody complex in the pathogenesis of the disease.